Whole genome sequencing of Plasmodium falciparum from dried blood spots using selective whole genome amplification. (December 2016) - Oyola, Samuel; Ariani, Cristina; Hamilton, William; Kekre, Mihir; Amenga-Etego, Lucas; Ghansah, Anita; Rutledge, Gavin; Redmond, Seth; Manske, Magnus; Jyothi, Dushyanth; Jacob, Chris; Otto, Thomas; et al.
Abstract Background Translating genomic technologies into healthcare applications for the malaria parasitePlasmodium falciparum has been limited by the technical and logistical difficulties of obtaining high quality clinical samples from the field. Sampling by dried blood spot (DBS) finger-pricks can be performed safely and efficiently with minimal resource and storage requirements compared with venous blood (VB). Here, the use of selective whole genome amplification (sWGA) to sequence theP. falciparum genome from clinical DBS samples was evaluated, and the results compared with current methods that use leucodepleted VB. Methods Parasite DNA with high (>95%) human DNA contamination was selectively amplified by Phi29 polymerase using short oligonucleotide probes of 8–12 mers as primers. These primers were selected on the basis of their differential frequency of binding the desired (P. falciparum DNA) and contaminating (human) genomes. Results Using sWGA method, clinical samples from 156 malaria patients, including 120 paired samples for head-to-head comparison of DBS and leucodepleted VB were sequenced. Greater than 18-fold enrichment ofP. falciparum DNA was achieved from DBS extracts. The parasitaemia threshold to achieve >5× coverage for 50% of the genome was 0.03% (40 parasites per 200 white blood cells). Over 99% SNP concordance between VB and DBS samples was achieved after excluding missing calls. Conclusion The sWGA methods described here provide a reliable and scalable way of generatingP. falciparum genome sequence data from DBS samples. The current data indicate that it will be possible to get good quality sequence on most if not all drug resistance loci from the majority of symptomatic malaria patients. This technique overcomes a major limiting factor inP. falciparum genome sequencing from field samples, and paves the way for large-scale epidemiological applications.